A Novel Hydroxamic Acid-Based Curcumin Derivative as Potent Histone Deacetylase Inhibitor for the Treatment of Glioblastoma - Wang, Hao; Shi, Lei; Wang, Zhimin (Frontiers in Oncology, 2021)
Glioblastoma (GBM) is one of the most common primary and deadliest malignant brain tumor with chemoresistance and poor prognosis. There is a lack of effective chemotherapeutic drug for the treatment of GBM. In this work, we reported the preparation of a HDAC inhibitor, DMC-HA, from the structural modification of natural product curcumin. DMC-HA were tested in a HDAC inhibition assay and an MTT assay for cytotoxicity. It showed potent inhibition of HDAC1-2, and HDAC6 with IC50 values in the submicromolar concentration range. DMC-HA significantly inhibited the proliferation of human glioblastoma U87 cells, and mediated apoptosis of U87 cells in a dose- and time-dependent manner. In addition, DMC-HA elevated the acetylation level of histone H3 in U87 cells. Pharmacokinetic studies showed that DMC-HA possessed acceptable pharmacokinetic profiles, accompanied with certain brain permeability. Lastly, we showed that DMC-HA suppressed the growth of tumor in U87 tumor xenograft model in vivo with no obvious toxicity. These results demonstrate that DMC-HA has the potential to be developed as a chemotherapeutic drug for GBM patients.